Gambaran Tingkat Kecemasan dalam Menghadapi Ujian Akhir Semester pada Siswa-Siswi SMPN 2 Loceret Kabupaten Nganjuk Tahun 2025 (Studi Kasus) - Niela, Oriza Sativa Alnidano Sakha Natha; Wijayanti, Endah Tri; Mudzakkir, Muhammad (Lembaga Publikasi Ilmiah Nusantara, 2025)
Anxiety is one of the most common mental disorders in human life and can affect anyone, regardless of age, gender, or social background. This study aims to describe the levels of anxiety experienced by students of SMPN 2 Loceret in facing last exams semester. This research design uses a descriptive quantitative approach, an approach that emphasizes the collection and analysis of data in the form of numbers or numerical data, which are then analyzed to describe a particular phenomenon. The results and discussion regarding the levels of anxiety experienced by students of SMPN 2 Loceret in facing last exams semester are presented in this chapter. To answer the research questions and achieve the research objectives, data collection and analysis were conducted, and the results outline the main findings. Tables, graphs, and statistics with detailed explanations accompany the findings from the data analysis, which followed the procedures outlined above. Based on the research results, it can be concluded that students experience varying levels of anxiety when facing final exams. Most students fall into the moderate anxiety category, followed by low anxiety, and only a small percentage experience high anxiety.